First catalog of spiders of Morocco (Arachnida: Araneae): A critical review of all spider species cited from Morocco with their localities - Benhalima, Souâd; Bosmans, Robert (Zootaxa, 2026)
Following the recent publication of the first checklist of spiders in Morocco recorded between 1840 and 2024 (Benhalima & Bosmans 2024), the authors have cataloged all the species mentioned and supplemented this list with others published up to January 2026. The authors present the first catalog of spider species in Morocco, documenting 638 species belonging to 246 genera and 47 families including 180 endemics. According to the World Spider Catalog (2026) and the present work, 63 species are not included, 7 species of dubious origin are not omitted from the catalog. For each species, a detailed list of all localities cited in the literature is provided, along with full references. All data are examined and critically analysed using the most recent available information.